До 70-річчя Руслана Пирога - Любарська, Л.В. (Архіви України, 2011)
Подано фотодокументи із фондів ЦДКФФА України ім. Г.С. Пшеничного,
які висвітлюють наукову і організаційну діяльність Р. Я. Пирога, а також
окреслюють окремі аспекти його роботи на посаді Голови Державного
комітету архівів України, зокрема його участь у міжнародних заходах. Представлены фотодокументы из фондов ЦГКФФА Украины
им. Г.С. Пшеничного,
которые освещают научную и организационную деятельность
Р. Я. Пырога, а также очерчивают отдельные аспекты его работы
на должности Председателя Государственного
комитета архивов Украины, в
частности его участие в международных
мероприятиях. There are given the documents of the Central State Archives of Film, Audio
and Visual Documents of Ukraine named after H.S. Pshenychnyi, that highlighted
the scientific and organizational activities of Ruslan Pyrih, as well as outlined some
aspects of his work as the Head of State Committee on Archives of Ukraine, in
particular his participation in international events.